2019
DOI: 10.1158/0008-5472.can-18-0236
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 Is a Therapeutic Target for Hypodiploid B-Lineage Acute Lymphoblastic Leukemia

Abstract: Acute lymphoblastic leukemia (ALL) is the most common cancer in children. The highest rates of treatment failure occur in specific genetic subsets of ALL, including hypodiploid B-cell ALL (B-ALL), for which effective alternative therapies to current intensive chemotherapy treatments have yet to be developed. Here, we integrated biochemical and genomic profiling with functional drug assays to select effective agents with therapeutic potential against hypodiploid B-ALL. ABT-199, a selective Bcl-2 inhibitor, was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 40 publications
(56 reference statements)
7
68
0
Order By: Relevance
“…Promising results have been reported in TCF3-PBX1 B-ALL [127] and in hypodiploid B-ALL [6,11], suggesting that Bcl2 inhibition could be a encouraging strategy also for the treatment of these B-ALL subtypes. In conclusion, all preclinical data on Bcl2 inhibition in ALL confirmed the therapeutic potential of Bcl2 inhibition for B-ALL patients.…”
Section: Bcl2mentioning
confidence: 97%
See 1 more Smart Citation
“…Promising results have been reported in TCF3-PBX1 B-ALL [127] and in hypodiploid B-ALL [6,11], suggesting that Bcl2 inhibition could be a encouraging strategy also for the treatment of these B-ALL subtypes. In conclusion, all preclinical data on Bcl2 inhibition in ALL confirmed the therapeutic potential of Bcl2 inhibition for B-ALL patients.…”
Section: Bcl2mentioning
confidence: 97%
“…A recent study showed that, in a B-ALL patient-derived xenograft (PDX) model, hypodiploid cells are sensitive to the B-cell lymphoma (Bcl) 2 inhibitor Venetoclax (ABT-199), suggesting that Bcl2 inhibition could be a promising strategy for the treatment of hypodiploid B-ALL [6,11].…”
Section: Hypodiploidymentioning
confidence: 99%
“…131 Preclinical studies have identified activities of venetoclax against high-risk leukemias such as ETP ALL, KMT2A-rearranged ALL, TCF3-HLF-positive ALL, and hypodiploid ALL (Table 2). 132,133 Proteasome and mTOR inhibitors have shown efficacy in relapsed ALL. 134,135 DOT1L, bromodomain, menin, and histone deacetylate inhibitors have shown promise in preclinical studies as therapies targeting unique molecular characteristics of KMT2A-rearranged ALL.…”
Section: Molecularly Targeted Agentsmentioning
confidence: 99%
“…Venetoclax plus chemotherapy is exhibiting good efficacy in adult refractory/relapsed T-ALL [159] . Additionally, preclinical studies have shown remarkable effectivity in childhood B-ALL [160] and the first phase I trials are currently developing, with encouraging results (NCT03181126) [161] .…”
Section: Other Pharmacogenes As Future Possibilities In the Field Of mentioning
confidence: 99%